Visually identified breakpoints in muscle oxygen saturation are not equivalent to ventilatory thresholds in national-level triathletes - Ignacio Fernández-Jarillo; Jordi Montraveta; Xavier Iglesias; Chris McManus; Philip Skotzke; Diego Chaverri (European Journal of Applied Physiology, 2026)
Purpose Portable near-infrared spectroscopy (NIRS) enables cost-effective monitoring of muscle oxygen saturation (SmO 2 ) during exercise, presenting a promising alternative for delineating exercise intensity domains. This study investigated whether SmO 2 breakpoints (BP 1 and BP 2 ) can provide accurate estimates of ventilatory thresholds (GET and RCP). Methods Twelve male Tier 3 triathletes completed an outdoor incremental TestVAM. Vastus lateralis SmO 2 was recorded using NIRS, alongside pulmonary gas exchange measurements. BP 1 and BP 2 were identified visually. Heart rate (HR) and running speed at BP 1 , BP 2 , GET, and RCP were extracted. The intraclass-correlation coefficient (ICC) was calculated and equivalence between SmO 2 breakpoints and ventilatory thresholds was assessed with equivalence bounds set at 5 bpm for HR and 0.5 km h −1 for speed. Results The ICC(3,1) abs was poor to moderate for all comparisons (range: 0.18–0.69). HR and speed between BP 1 and GET were not equivalent ( p > 0.91), with GET occuring ealier in both HR ( p = 0.014, Δ = − 9.92 bpm, 90% CI [ − 16, − 3.83]) and speed ( p = 0.007, Δ = − 1.29 km h −1 , 90% CI [ − 1.99, − 0.59]). Similarly, BP 2 and RCP were not equivalent ( p > 0.98), and both HR (Δ = − 9.3 bpm, 90% CI [ − 12.18, − 6.42]) and speed (Δ = − 1.75 km·h −1 , 90% CI [ − 2.33, − 1.17]) occuring earlier at RCP ( p Conclusion In this sample, SmO 2 breakpoints did not fullfill criterion validity against ventilatory thresholds and therefore should not be used for determining exercise intensity domains. Further research should evaluate their equivalence using robust detection methodologies in larger samples.